Risk Factors of Hypertension Among Elderly in Indonesia: Systematic Review - Wardani, Hamidah Retno; Mustapa, Gesit Wira; Susanto, Tantut; Asmaningrum, Nurfika (Universitas Malahayati, 2024)
ABSTRACT Elderly is the stage in which the function of the organs of the body begins to decline. Old age is associated with a decrease in physical capacity for life and individual sensitivity. Elderly is a vulnerable group because the elderly are people whose health problems are decreasing because of the increase in age experienced by the aged resulting in all systems and functions undergoing a decrease of one of non-communicable diseases namely hypertension. This study aims to analyze risk factors for hypertension in the elderly in Indonesia Methods: Study conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Data obtained from nine journals that have been screened. A total of 220 journals were obtained using the search methods of google scholar and crossreff journalism. The results show that the risk factors associated with the incidence of hypertension in the elderly include gender, BMI, genetic, age, job, obesity, income, family history, physical activity, cholesterol levels, diet, smoking, past history of high blood pressure, and salt consumption. Hypertension is a disease that can be influenced by risk factors which can be changed and cannot be changed. Then it is necessary to know about any risk factors that can influence the occurrence of hypertension in the elderly. Keywords: Risk Factors, Hypertension, Elderly, Indonesia